'She done Coriolanus at the Convent': Empowerment and Entrapment in Teresa Deevy's In Search of Valour. Issue 2 (November 2019) - Maley, Willy
Abstract : This article explores the gender politics of a neglected one-act play by Teresa Deevy, first staged at the Abbey in 1931, that revolves around the young female protagonist's recollection of a convent production of Shakespeare's Coriolanus in which the title role was taken by a young woman. This role model offers inspiration for a character confined as a domestic servant and defiantly seeking an alternative to the stultifying circumstances of life in rural Free State Ireland. While Ellie Irwin resembles other spirited Deevy heroines, the doubling of the young servant with her memory of Charlotta Burke as a non-cross-dressed Coriolanus adds a different dramatic dimension and raises questions of gender performance that the play's critical reception has not always acknowledged.